Genetic diversity and population structure in casanareño colombian cattle through microsatellite molecular markers - Ocampo, Ricardo Jose; Martinez Rocha, Juan Felipe; Martinez Sarmiento, Rodrigo Alfredo (Ecosistemas y Recursos Agropecuarios, 2020)
Knowledge of population structure, genetic variability and introgression of foreign breeds is crucial to focus efforts for the conservation of indigenous genetic resources. This study aimed to analyze the genetic diversity of six Casanareño populations cattle using 11 microsatellite markers. Blood samples were obtained from 212 unrelated individuals which were amplified by PCR and analyzed. We observed a total of 156 alleles with a polymorphic information content average of 0.742, which shows that the panel used was very informative. The observed heterozygosity estimates varied from 0.788 in MF to 0.690 in CY. There was a deficit of heterozygous individuals in the general population (FIS = 0.059) caused by high consanguinity and the proportion of the genetic variance due to the differences between the different subpopulations was 4%. Both the Bayesian grouping analysis and the phylogenetic tree showed a reliable clustering pattern, which revealed two main clusters in Casanareño cattle which can be the result of geographical isolation, reproductive practices and absorption to zebu breeds. Four out of six subpopulations presented effective population sizes below the critical level defined by the FAO of 50 individuals, so it is recommended to form a conservation nucleus of the Casanareño breed with a well-defined mating scheme to minimize consanguinity and the intensive use of few males to maintain genetic diversity and prevent the breed from becoming extinct.